2018
DOI: 10.3126/jnarc.v4i1.19686
|View full text |Cite
|
Sign up to set email alerts
|

Milling, Nutritional, Physical and Cooking Properties of Four Basmati Rice Varieties

Abstract: Rice is one of the most popular staple foods produced contributing higher most in agriculture gross domestic production in Nepal. Thus, nutritional, physicochemical, and cooking properties of rice might interplay important roles in their production and farming practice, therefore, it is inevitable to understand these characteristic features. However, there has been only limited information available on such properties, therefore we aimed to examine nutritional, physicochemical and cooking properties of four Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The highest protein content was found in Kajalshail and lowest in Carandol. This result agrees with earlier findings by Ojha et al (2018), they found that protein content ranged from 6.50 to 7.74% and 7.77 to 11.48% on evaluation of indigenous rice cultivar in India. Matin et al (2017) conducted an study on 19 Bangladeshi HYV rice varieties released by BRRI and observed protein content varied from 6.2 to 9.3% that also similar to our present study.…”
Section: Protein Iron and Zinc Content Of The Rice Varietiessupporting
confidence: 93%
“…The highest protein content was found in Kajalshail and lowest in Carandol. This result agrees with earlier findings by Ojha et al (2018), they found that protein content ranged from 6.50 to 7.74% and 7.77 to 11.48% on evaluation of indigenous rice cultivar in India. Matin et al (2017) conducted an study on 19 Bangladeshi HYV rice varieties released by BRRI and observed protein content varied from 6.2 to 9.3% that also similar to our present study.…”
Section: Protein Iron and Zinc Content Of The Rice Varietiessupporting
confidence: 93%
“…High-amylose rice grains increase their volume and become flaky during cooking, but harden when cooling. Rice varieties with high-amylose content are more prone to solid loss during cooking as increased starch leaches out from the starch granules (Ojha et al 2018;Tong et al 2019). Low-amylose basmati is preferred for consumption due to its aromatic, soft, and sticky texture after cooking.…”
Section: Introductionmentioning
confidence: 99%
“…Low-amylose basmati is preferred for consumption due to its aromatic, soft, and sticky texture after cooking. Therefore, cooking, eating and flour properties of rice flours can be improved by blending a low-amylose rice cultivar with some highamylose cultivars (Zhou et al 2002;Noda et al 2003;Ojha et al 2018) which may provide a desirable paste characteristic for special food applications. Although the low-amylose rice flour has many potential applications in the bakery and confectionery industries, the rheological characteristics of rice flour determine its application as a raw material for the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…The water absorption coefficient was maximum, 3.11, in black basmati and minimum, 2.18, in red basmati. [4].…”
Section: Introductionmentioning
confidence: 99%